The Effect of Economic and Social Infrastructure on Household Food Security in Indonesia - Sari, Dyah Wulan; Yudha, Putri Candra Anggi; Restikasari, Wenny (Jurnal Ekonomi Indonesia, 2019)
Food is a basic requirement for living things. This study aims to analyze the effects of economic infrastructure, social infrastructure and household characteristics on food security in Indonesia using the Johnsson and Toole (1991) methods. There were 285,908 households studied originating from the 2015 SUSENAS data. The model used in this study was the general ordered logistics model. Based on the results of the study there were 29.51% of food security, 25.12% of vulnerable food, 23.14% of food shortages and 22.33% of households at food insecurity. The results of this study also revealed that ownership of transportation modes, electricity use, fuel use, education of household heads and household health insurance significantly affected food security. The government program in the form of giving poor rice (RASKIN) provides poor results reducing the chance offood security by 11% and increasing the chances of food insecurity by 6%.